High-risk Behavior Among U.S. Military HIV-Infected Active-Duty and Retired Personnel. (4th October 2017) - Pannebaker, Danielle; Larson, Derek; Wang, Xun; Ganesan, Anuradha; Okulicz, Jason; Schofield, Christina; O'Bryan, Thomas; Agan, Brian; Deiss, Robert
Abstract: Background: Despite a high incidence of sexually transmitted infections (STIs), sexual behavior among U.S. military personnel remains understudied. Since 2014, the U.S. Military HIV Natural History Study has administered a behavioral questionnaire to a cohort of HIV-infected active-duty (AD) and retired personnel (RP). We compared patterns of risk behavior between AD and RP. Methods: Male participants who completed a behavioral questionnaire ( n = 1, 465) were included in this study. Chi-square and stepwise logistic regression were used to compare AD with RP. Our model included all behavioral variables listed below with adjustment for age and race. We assumed a priori that duty status would be correlated with age and selected the former as our variable of interest, hypothesizing that AD would engage in a higher number of risk behaviors. Results: Selected demographics and behavioral data are summarized below. Conclusion: In contrast with our hypothesis, we found a high prevalence of sexual risk behavior among both AD and RP, and only lifetime use of hard drugs was independently associated with duty status. Despite high STI rates, 20% in either group reported high self-perceived risk for STIs and/or recent condomless sex with an anonymous partner. Our findings demonstrate a need for intensive STI screening and counseling among HIV-infected military personnel in multiple career stages. Disclosures: All authors: No reported disclosures.